THE EFFECTIVENESS OF TASK BASED LEARNING MODEL ON WRITING NEWS ITEM TEXT AT XI GRADE MAN 3 PADANG PANJANG - RINI HENDRITA (FKIP UMSB, 2019)
This research aimed at describing the effectiveness of TBL model on writing especially on news item text. The research design used was pre-experimental research with one group model. The population of this research was the entire XI grade of MAN 3 Padang Panjang. The sample of this research was one class; XI Science students. To determine the sample, the researcher used purposive sampling technique. To gain the data, this research used pre-test and post-test. The comparison of pre-test and post-test result is 43.57%, the mean of pre-test is 46 % and it increases to 80.47% to the post test one. Then, hypothesis showed that t-count is higher than t-table (8.74 > 1,761). It means task based learning model (TBL) has significant effectiveness on writing news item text. To conclude the result of this research, it can be stated that TBL model have been successful to be effective method and successful to increase students achievement in writing news item text. This research is recommended for teacher to use TBL in teaching writing especially on news items text. Keywords: News item text, task based learning model, writing